Measuring lateropulsion following stroke in the clinical setting: exploring the measurement, nature and recovery of lateropulsion using Wii technologies and clinical measures - Birnbaum, Melissa Ann (Curtin University, 2021)
This thesis explored the measurement of lateropulsion following stroke in clinical research, extending our knowledge about the nature and recovery of this postural control disorder. The thesis focused on three areas: (1) the measurement properties of clinical lateropulsion and sitting balance measures in stroke survivors; (2) the use of Wii Balance Board(s) as an instrumented postural control measure in sitting and standing in individuals with lateropulsion; and (3) the longer-term outcomes of individuals with lateropulsion.